Discovering the Potential of Dental Pulp Stem Cells for Corneal Endothelial Cell Production: A Proof of Concept - Bosch, Begoña M.; Salero, Enrique; Núñez-Toldrà, Raquel; Sabater, Alfonso L.; Gil, F. J.; Perez, Roman A. (Frontiers in Bioengineering and Biotechnology, 2021)
Failure of corneal endothelium cell monolayer is the main cause leading to corneal transplantation. Autologous cell-based therapies are required to reconstruct in vitro the cell monolayer. Several strategies have been proposed using embryonic stem cells and induced pluripotent stem cells, although their use has ethical issues as well as limited clinical applications. For this purpose, we propose the use of dental pulp stem cells isolated from the third molars to form the corneal endothelium cell monolayer. We hypothesize that using dental pulp stem cells that share an embryological origin with corneal endothelial cells, as they both arise from the neural crest, may allow a direct differentiation process avoiding the use of reprogramming techniques, such as induced pluripotent stem cells. In this work, we report a two-step differentiation protocol, where dental pulp stem cells are derived into neural crest stem-like cells and, then, into corneal endothelial-like cells. Initially, for the first-step we used an adhesion culture and compared two initial cell sources: a direct formation from dental pulp stem cells with the differentiation from induced pluripotent stem cells. Results showed significantly higher levels of early stage marker AP2 for the dental pulp stem cells compared to induced pluripotent stem cells. In order to provide a better environment for neural crest stem cells generation, we performed a suspension method, which induced the formation of neurospheres. Results showed that neurosphere formation obtained the peak of neural crest stem cell markers expression after 4 days, showing overexpression of AP2, Nestin and p75 markers, confirming the formation of neural crest stem-like cells. Furthermore, pluripotent markers Oct4, Nanog and Sox2 were as well upregulated in suspension culture. Neurospheres were then directly cultured in corneal endothelial conditioned medium for the second differentiation into corneal endothelial-like cells. Results showed conversion of dental pulp stem cells into polygonal-like cells expressing higher levels of ZO-1, ATP1A1, COL4A2 and COL8A2 markers, providing a proof of the conversion into corneal endothelial-like cells. Therefore, our findings demonstrate that patient-derived dental pulp stem cells may represent an autologous cell source for corneal endothelial therapies that avoids actual transplantation limitations as well as reprogramming techniques.